Community acquired pneumonia as a risk factor for cardiovascular diseases - Nuñez-Delgado, Rocio del Pilar (2022)
Background: Community-acquired pneumonia produces inflammatory products that produce preventable cardiovascular events. Objective: To establish if Community-Acquired Pneumonia (CAP) is a risk factor associated with cardiovascular disease. Materials and Methods: A cohort design was carried out with: patients hospitalized for a diagnosis of CAP and a control group without pneumonia (1:2), who met the selection criteria. Chi square, Relative Risk and confidence intervals were calculated for the crude and adjusted bivariate analysis and robust multivariate analysis. Results: Of the total study population, 693 patients were analyzed. The mean age was 64.1 ± 13.7 (SD) years. The most were male (61.5%). Among the classic cardiovascular factors, 96.8% used tobacco; 73.9% were hypertensive; 82.5% were diabetic and 96.5% were hypercholesterolemic. It was found that men had a higher frequency of acute coronary syndrome than women (22.3% vs. 4.5%; p<0.01), as well as in heart failure (33.1% vs. 25.8%; p<0.01) and in greater arrhythmia in women (23.2% vs 13.4%; p<0.01). In the multiple regression analysis, the observed association was preserved; adjusting with the confounding covariates of tobacco consumption, arterial hypertension, diabetes mellitus and hypercholesterolemia, for acute coronary syndrome: (RR= 3.98; 95% CI: 2.98-5.33), heart failure: (RR= 9, 65; 95% CI: 8.45-11.0) and arrhythmias: (RR= 10.7; 95% CI: 8.64-13.2). Conclusion: CAP is a risk factor associated with cardiovascular disease.